1996
DOI: 10.1002/art.1780390612
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of bacterial DNA in venereal‐associated arthritis

Abstract: Objective. To evaluate the utility of polymerase chain reaction (PCR) amplification in detecting DNA from venereal-associated microorganisms in the synovial fluid of patients with inflammatory arthritis.Methods. Oligonucleotide primers were developed for nested PCR based on Chlamydia, Ureaplasma, and Neisseria DNA sequences. PCR products were detected by gel electrophoresis and dot-blot hybridization. Primers specific for the target bacterial DNA were used to search for bacterial DNA in 61 synovial fluid speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 31 publications
0
26
0
6
Order By: Relevance
“…Specimens for PCR were transported on dry ice, and DNA was extracted the following day for testing by sensitive and specific assays, as described previously (10)(11)(12), for subsequent PCR for C trachomatis 16S ribosomal RNA (rRNA), and major outer membrane protein (MOMP) (10,12) and for several other organisms. Chlamydia pneumoniae 16S rRNA and MOMP were assessed using 2 sets of primers as described (13,14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens for PCR were transported on dry ice, and DNA was extracted the following day for testing by sensitive and specific assays, as described previously (10)(11)(12), for subsequent PCR for C trachomatis 16S ribosomal RNA (rRNA), and major outer membrane protein (MOMP) (10,12) and for several other organisms. Chlamydia pneumoniae 16S rRNA and MOMP were assessed using 2 sets of primers as described (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…Borrelia burgdorferi outer surface protein A (OspA) was tested for using published primers for OspA and a genomic sequence (15) and using nested primers as described for OspA and OspB (16). Pan bacterial 16S rRNA was assessed using a conserved sequence present across all bacteria using published primers developed by Li et al (11) and by our group (17). For all assays for all organisms targeted, extreme care was taken to avoid crosscontamination of samples or assay preparations; that is, nucleic acids were prepared for analyses in a laboratory distant from that in which the PCR screening assays were prepared and run; separate sets of pipettors were used for DNA preparation and assay setup.…”
Section: Methodsmentioning
confidence: 99%
“…To address this issue, several laboratories have used broad-range PCR systems to search for bacterial DNA in synovial materials; most studies targeted SF, and samples from patients with a range of arthritides were analyzed (e.g., see refs. [16][17][18][19][20][21]. With minor exceptions, these studies indicated that DNA from many bacterial groups could be found in the joints of at least some patients.…”
mentioning
confidence: 96%
“…The characteristics of the gene marker HLA-B27 are being further defined. These genes seem to play a role in influencing immune function [14]. It is anticipated that by understanding the effects of each of these known genes, researchers will make significant progress in discovering a cure for ankylosing spondylitis.…”
Section: Resultsmentioning
confidence: 99%